Equipping Teachers for Success in Rural Communities: Unveiling the Key Characteristics and Attributes of Thriving Rural Teachers - Tania Leach; Ondine Bradbury (Education Sciences)
Australian education faces persistent challenges in preparing and retaining teachers within rural contexts. This qualitative study examines the attributes of thriving rural teachers through focus group discussions with 103 rural educational leaders. Utilising a theoretical framework combining attribution theory and ecological systems perspectives, the study synthesised leaders’ perceptions of key dispositions and behaviours contributing to rural teachers’ success. Four interconnected dimensions emerged: being community, classroom, professionally and personally equipped. This study revealed that while individual teacher attributes are crucial, school support and community context significantly influence teacher success. The application of attribute theory further revealed that findings attributed teacher’s success to internal, stable, and controllable factors, suggesting that key traits could be developed through targeted professional development and experience. This study provides nuanced insights into ’rural readiness’, informing education policy decisions and practices, initial teacher education institutions, schools, and communities. The study emphasises the need for a holistic approach to teacher preparation and support that considers both individual and systemic factors.